Relationship Between Optimism and Health Under the Influence of Religious Beliefs in Two Latin American Population Samples [Relación Entre Optimismo y Salud Bajo la Influencia de Las Creencias Religiosas en Dos Muestras Latinoamericanas] - Vera-Villarroel, P; Contreras-Ramirez, D; Lillo-Vidal, S (Fundacion para el Avance de la Psicologia, 2017)
The study of well-being has gained increasing relevance given its relationship with psychological states such as anxiety, depression, stress, as well as health. Nonetheless, there are few explanatory proposals on well-being, or any empirical cross-cultural validation of these. The present study evaluated the effect of the inclusion of a cultural contextual variable on an explanatory model of well-being, specifically on whether religious beliefs moderate the mediating effect of the positive affects on the relationship between optimism and health. The sample of this study consisted of 529 participants from two Latin American countries (285 from Chile and 244 from Colombia). The results indicate that, in both countries, there is a significant effect of optimism on the perception of health mediated by positive affects. However, religious beliefs do not exert a significant effect on the intensity of the relationships between the variables of the base model. The importance of cultural factors and cross-cultural studies on well-being are presented and discussed. © 2017 Fundación Universitaria Konrad Lorenz